La tradition des autobiographies chantées chez les Sharanahua (Amazonie occidentale) - Pierre Déléage (Bulletin de l'Institut Français d'Études Andines, 2008)
The Sharanahua (a Panoan people of Western Amazon) maintain a tradition of autobiographical songs. Two transcriptions and translations of such songs are presented here. A detailed analysis highlights two main problems. These songs narrate very personal memories, but are couched in an extremely stereotypical language; secondly, they are presented as simultaneous quotations of past speech of the singer and as faithful repetitions of taught words. This text explores the implications of these apparent paradoxes.